2019
DOI: 10.3390/ijerph16203807
|View full text |Cite
|
Sign up to set email alerts
|

Injury-Related Behavioral Variables in Alpine Skiers, Snowboarders, and Ski Tourers—A Matched and Enlarged Re-Analysis

Abstract: Behavioral variables might play an important role in explaining the differences in injury rates across winter sport disciplines and injury prevention programs might be more specifically designed based on this knowledge. On ski slopes, alpine skiing, snowboarding, and ski touring are the predominant winter sport disciplines. Therefore, the aim of the present study was to investigate possible differences in injury-related behavioral variables between practitioners of these disciplines. Using a matched re-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Not disclosing a concussion at the time of injury impacts injury outcomes at all sporting levels (Broglio et al, 2010;Kerr et al, 2016;Llewellyn et al, 2014;McCrea et al, 2004;Meehan et al, 2013) and was reported by 21.9% of student-athletes in the current study. Results from the current study are consistent with previous literature investigating the association between sensation-seeking and engaging in high physical risk athletic activities (Goma-i-Freixanet et al, 2012;Graupensperger et al, 2019;Martin-Diener et al, 2016;Niedermeier et al, 2019). Specifically, sensation-seeking is associated with increased overall athletic injury risk (Martin-Diener et al, 2016); engaging in high physical risk sports such as mountain climbing, rock climbing, white-water rafting, skiing, and snowboarding (Martin-Diener et al, 2016); and reporting an injury history (Goma-i-Freixanet et al, 2012).…”
Section: Sensation-seeking and Concussion Care-seeking/disclosure Outcomessupporting
confidence: 92%
“…Not disclosing a concussion at the time of injury impacts injury outcomes at all sporting levels (Broglio et al, 2010;Kerr et al, 2016;Llewellyn et al, 2014;McCrea et al, 2004;Meehan et al, 2013) and was reported by 21.9% of student-athletes in the current study. Results from the current study are consistent with previous literature investigating the association between sensation-seeking and engaging in high physical risk athletic activities (Goma-i-Freixanet et al, 2012;Graupensperger et al, 2019;Martin-Diener et al, 2016;Niedermeier et al, 2019). Specifically, sensation-seeking is associated with increased overall athletic injury risk (Martin-Diener et al, 2016); engaging in high physical risk sports such as mountain climbing, rock climbing, white-water rafting, skiing, and snowboarding (Martin-Diener et al, 2016); and reporting an injury history (Goma-i-Freixanet et al, 2012).…”
Section: Sensation-seeking and Concussion Care-seeking/disclosure Outcomessupporting
confidence: 92%
“…Since 63% of freestyle skiers/snowboarders [ 17 ] and 38% of the slope snowboarders [ 16 ] were unaware of the existence of FIS rules, campaigns to more effectively communicate the safety rules in ski resorts are recommended by the authors. In another study, snowboarders showed a higher sensation seeking and a self-reported alcohol consumption compared to downhill skiers or ski tourers [ 18 ], which strengthens the assumption that snowboarders remain an important risk group for injury prevention programs. However, sensation seeking seems to be an important behavioral variable generally, since higher sensation seeking scores were found in injured winter sports practitioners compared to uninjured winter sports practitioners [ 18 ].…”
Section: Potential Risk Factors For Injuries In Skiing and Snowboamentioning
confidence: 59%
“…In another study, snowboarders showed a higher sensation seeking and a self-reported alcohol consumption compared to downhill skiers or ski tourers [ 18 ], which strengthens the assumption that snowboarders remain an important risk group for injury prevention programs. However, sensation seeking seems to be an important behavioral variable generally, since higher sensation seeking scores were found in injured winter sports practitioners compared to uninjured winter sports practitioners [ 18 ]. Helmet usage is strongly recommended in nearly all mountain sports activities.…”
Section: Potential Risk Factors For Injuries In Skiing and Snowboamentioning
confidence: 59%
“…In this cross-sectional study the data collection occurred through each ski club, which was very labor intensive from the researchers and the club personnel perspectives. Similar to previously published studies in winter sports (Niedermeier et al, 2019), we acknowledge the limitations connected to a cross-sectional study based on self-reports (e.g., impossible to assess causal relationships, nontruthfully answered questions, or a potential recall bias). The implementation of a centralized system through the ASSA or Alpine Canada Association with an online version of the baseline medical questionnaire would streamline the process.…”
Section: Strengths and Limitationsmentioning
confidence: 89%